The Mediating Effect of Smartphone Addiction on Students' Academic Performance - Bharata, Wira; Widyaningrum, Premi Wahyu (Jurnal Manajemen, 2021)
This study identify the factors that influence the academic performance of students in Indonesia. Ease of use and social anxiety are considered antecedents of smartphone addiction. Data was collected through an online survey of 100 respondents who were students in the city of Malang. Data analysis using GSCA software. The findings of this study prove that ease of use and social anxiety have an impact on increasing smartphone addiction behavior. It also reveals the mediating effect of smartphone addiction playing an important role in students' academic performance. It is recommended that further researchers can also elaborate on this research model, especially with regard to the concept of smartphone addiction.